Current sheet scattering and ion isotropic boundary under 3‐D empirical force‐balanced magnetic field. Issue 10 (16th October 2014) - Yue, Chao; Wang, Chih‐Ping; Lyons, Larry; Liang, Jun; Donovan, Eric F.; Zaharia, Sorin G.; Henderson, Michael
Abstract To determine statistically the extent to which current sheet scattering is sufficient to account for the observed ion isotropic boundaries (IBs) for <30 keV ions, we have computed IBs from our 3‐D empirical force‐balanced magnetic field, identified IBs in FAST observations, and investigated the model‐observation consistency. We have found in both model and FAST results the same dependences of IB latitudes on magnetic local time, ion energy, Kp, and solar wind dynamic pressure (PSW) levels: IB moves to higher latitudes from midnight toward dawn/dusk and to lower latitudes as energy increases and as Kp or PSW increases. The model predicts well the observed energy dependence, and the modeled IB latitudes match fairly well with those from FAST for Kp = 0. As Kp increases, the latitude agreement at midnight remains good but a larger discrepancy is found near dusk. The modeled IBs at the equator are located around the earthward boundary of highly isotropic ions observed by Time History of Events and Macroscale Interactions during Substorms at midnight and postmidnight, but with some discrepancy near dusk under high Kp. Thus, our results indicate that current sheet scattering generally plays the dominant role. The discrepancies suggest the importance of pitch angle scattering by electromagnetic ion cyclotron waves, which occur more often from dusk to noon and are more active during higher Kp. The comparison with the observed IBs is better with our model than under the nonforce‐balanced T89, indicating that using a forced‐balanced model improves the description of the magnetic field configuration and reinforces our conclusions regarding the role of current sheet scattering.